Human papillomaviruses and cervical cancer from the perspective of the World Health Organisation initiative for cervical cancer elimination - Filipić, Brankica; Rapajić-Moran, Ivana; Nikolić, Ines; Oljačić, Slavica; Mandić, Aljoša (Archives of Pharmacy, 2024)
Human papillomaviruses (HPV) are the most common sexually transmitted pathogens worldwide, leading to infections with a wide range of clinical manifestations: from benign conditions to different types of cancer in women and men as well. Cervical cancer is highly correlated with persistent high-risk-HPV (HR-HPV) infection, which is the key factor in emergence of 99.99% of cervical cancer cases. The most effective way to prevent HPV-related cancers is vaccination. There are three available prophylactic HPV vaccines: bivalent, quadrivalent and nonavalent. The nonavalent vaccine is gradually replacing other HPV vaccines in most countries and can be given from year 9, but it is commonly routinely implemented at the age of 11 to 12. The World Health Organization has recognised cervical cancer as a global threat and has announced the so-called 90-70-90 strategy to reduce and even eliminate cervical cancer. This strategy implies that 90% of girls should be vaccinated by the age of 15, 70% of women should be screened for cervical cancer, and 90% of women diagnosed with cervical disease should receive adequate treatment. Although different treatment options are available: surgery, radiation therapy, chemotherapy, and advanced target therapy using monoclonal antibodies, great efforts are needed to achieve the goals set by the World Health Organization to eliminate cervical cancer.
Keywords: high-risk HPV (HR-HPV) infection; cervical cancer; HPV vaccination